The pharmacokinetic, safety, and tolerability profiles of eslicarbazepine acetate are comparable between Korean and White subjects. Issue 9 (21st June 2022) - Hwang, Sejung; Lee, Soyoung; Kim, Eunwoo; Hwang, Inyoung; Cho, Joo‐Youn; Chung, Jae‐Yong; Jang, In‐Jin; Oh, Jaeseong
Abstract: Eslicarbazepine acetate (ESL) is a prodrug antiseizure medication for the treatment of focal seizures. ESL shows a well‐established pharmacokinetic (PK)‐pharmacodynamic relationship and has similar extrinsic epilepsy‐related factors across ethnicities. This study evaluated and compared ESL safety, tolerability, and PK characteristics between Korean and White subjects. A randomized, double‐blind, placebo‐controlled, single‐ and multiple‐dose escalation study was conducted in healthy Korean and White adults. Participants randomly received a single dose and multiple oral doses of ESL (400–1600 mg) or placebo once daily for 11 days at a ratio of 8:2. Serial blood samples were collected to determine the plasma concentration of ESL and its metabolites (eslicarbazepine, [R‐licarbazepine and oxcarbazepine). Safety and tolerability were assessed throughout the study. A total of 29 Korean and 20 White subjects completed the study. The PK profiles of the metabolites of ESL were similar between Korean and White subjects. The geometric mean ratio (90% confidence interval) of Korean to White subjects for the area under the concentration–time curve within a dosing interval of eslicarbazepine was 1.06 (0.97–1.17) and 0.96 (0.87–1.06) after multiple oral doses of 400 and 1600 mg ESL, respectively. Other PK parameters were also similar between the two ethnic groups. ESL was well‐tolerated in healthy Korean and White subjects, and its PK characteristics were similar between the two ethnic groups. The results of this study support to use the same dosage regimen of ESL in both White and Korean patients with seizures.